ORGANIZATION AND METHOD FOR THE REMOTE LABORATORY WORK OF GENERAL TECHNICAL DISCIPLINE - Alfia Sh. Salakhova (Otkrytoe Obrazovanie (Moskva), 2016)
The article is devoted to the important problem – use of distant technologies in engineering education in the laboratory experiments. The role of distant experiment in the modern engineering education is discussed. The authors consider structure of the distant system to real experiments control and the method of realization distant laboratory work in the educational process. The analysis of distant laboratory work effectiveness is discussed.